Mars - Rake, Jody Sullivan (2021)
"Mars is famous for its coloring, but the fourth planet from the sun has more than that going for it. Discover more interesting facts and secrets about the famous "red planet.""--
The red planet -- Close but so far -- Too cold! -- Rocky landscape -- Wheeled explorers of Mars -- Could we live on Mars?.
"Pebble explore."
Includes bibliographical references and index.
Ages 6-8
Grades K-1
Keywords: Mars (Planet) -- Juvenile literature